Vers une Transition Alimentaire en Tunisie - Alary, Veronique; Frija, Aymen; M'hamed, Hatem Cheikh (International Center for Agricultural Research in the Dry Areas, 2023)
This presentation forms an integral part of a comprehensive training program designed for senior agricultural staff in Tunisia, focusing on the agroecological initiative. The primary objective is to acquaint participants with the agroecology transition, as exemplified by the OneCGIAR initiative. The presentation aims to impart both knowledge and practical skills, equipping attendees with a profound understanding of the fundamental principles of agroecology, living landscapes, and transition pathways. By enhancing their comprehension of these concepts, the training endeavors to empower participants to make well-informed decisions and implement sustainable practices within their respective agricultural contexts. Ultimately, this training contributes significantly to fostering participants' motivation, engagement, and a proactive commitment to advancing a global movement for ecologically harmonious and socially equitable agriculture. The ProSol Project in Tunisia collaborates with the CGIAR Initiative on Agroecology to organize this training.